Utilising Learning Environment Assessments to Improve Teaching Practices Among In-service Teachers Undertaking a Distance-Education Programme - Aldridge, Jill; Fraser, Barry; Ntuli, Sipho (Foundation for Education Science and Technology, 2009)
We examined the viability of using feedback from a learning environment instrument to guide improvements in the teaching practices of in-service teachers undertaking a distance-education programme. The 31 teachers involved administered a primary school version of the What Is Happening In this Class? (WIHIC–Primary) questionnaire to their 1,077 learners in order to determine preferred and actual classroom environments. Feedback about discrepancies between learners’ actual preferred learning environments were used to formulate teaching strategies to reduce discrepancies over a 12-week intervention period. In-service teachers’ reports, contact sessions, interviews between teachers and researchers, and three case studies based on classroom visits (one of which is reported here) provided thick descriptions of teachers’ reactions to utilising the learning environment instrument. Our research provided the first learning environment study at the primary school level in South Africa, cross-validated an IsiZulu version of the WIHIC when used for the first time in South Africa, and supported the success of teachers’ use of a learning environment questionnaire in guiding improvements in their teaching.